Case Report: Absence of Thyrocervical Trunk - Hassan Hassani Bafrani; Homayun Naderian; Mohammad Ali Atlasi; Abolfazl Azami-Tameh (Negah Institute for Scientific Communication, 2015)
The thyrocervical trunk most commonly arises from the upper portion of the first segment of the subclavian artery, close to the medial edge of the scalenus anterior muscle and after short distance is divided to the inferior thyroid, transverse cervical, and suprascapular artery. This study reports important variations in branches of the thyrocervical trunk in a singular female cadaver. On the right side, no thyrocervical trunk was found. The two branches which normally originate from the thyrocervical trunk had a different origin. The superficial cervical, suprascapular and internal thoracic arteries arose from the common trunk artery. An awareness of this rare variation is important because this area is used for diagnostic and surgical procedures.